2010
DOI: 10.1021/nl1016909
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/siRNA Nanoparticles Biofunctionalize Nerve Implants and Enable Neurite Outgrowth

Abstract: Microstructured 20 μm thick polymer filaments used as nerve implants were loaded with chitosan/siRNA nanoparticles to promote nerve regeneration and ensure local delivery of nanotherapeutics. The stable nanoparticles were rapidly internalized by cells and did not affect cell viability. Target mRNA was successfully reduced by 65-75% and neurite outgrowth was enhanced even in an inhibitory environment. This work, thus, supports the application of nanobiofunctionalized implants as a novel approach for spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 48 publications
0
60
1
1
Order By: Relevance
“…However, on the contrary of what was described in the first study, particle size was shown to be dependent on chitosan Mw, between 20 and 200 kDa [16]. The proportional correlation between particle size and Mw has been documented in several other works [67,81], although in some cases smaller particle sizes were reported with increasing Mw of chitosan (from 140 to 250 kDa), possibly due to increased inter-chain connections between longer chitosan molecules [82]. Surprisingly, in this latter study, this difference in particle size did not significantly affect transfection efficiency; also implying that Mw did not induce differences in the transfection level.…”
Section: Effect Of Chitosan Molecular Weightcontrasting
confidence: 68%
See 1 more Smart Citation
“…However, on the contrary of what was described in the first study, particle size was shown to be dependent on chitosan Mw, between 20 and 200 kDa [16]. The proportional correlation between particle size and Mw has been documented in several other works [67,81], although in some cases smaller particle sizes were reported with increasing Mw of chitosan (from 140 to 250 kDa), possibly due to increased inter-chain connections between longer chitosan molecules [82]. Surprisingly, in this latter study, this difference in particle size did not significantly affect transfection efficiency; also implying that Mw did not induce differences in the transfection level.…”
Section: Effect Of Chitosan Molecular Weightcontrasting
confidence: 68%
“…Surprisingly, in this latter study, this difference in particle size did not significantly affect transfection efficiency; also implying that Mw did not induce differences in the transfection level. Nevertheless, transfection was more effective than that of the commercial Lipofectamine  control [82]. Likewise, other authors report that the transfectability of complexes composed of chitosan or trimethyl chitosan/siRNA in HEK293 cells was independent of chitosan Mw (42-400 kDa, DD = 84-88%) [27].…”
Section: Effect Of Chitosan Molecular Weightmentioning
confidence: 90%
“…(2008) haveshownthatintracavitary implantation of chitosan guidance channels containing peripheral nerve grafts after subacute SCI resulted in a thicker bridge containing a larger number of myelinated axons compared with chitosan channels alone. Peripheral nervefilled chitosan conduits showed an excellent biocompatibility with the adjacent neural tissue with no signs of degradation and minimal tissue reaction at 14 weeks after implantation (Nomura, Baladie, et al, 2008).…”
Section: Chitosan For Central Nervous System Repairmentioning
confidence: 99%
“…Moreover, microstructured polymer filaments used as a nerve implant have been successfully loaded with chitosan/siRNA nanoparticles to promote nerve regeneration and ensure local delivery of nanotherapeutics. The nanoparticles were internalized by the cells resulting in target mRNA reduction and enhanced neurite outgrowth (Mittnacht et al, 2010). Pfister et al reported that NGF release kinetics could be regulated by embedding NGF at different radial locations within a nerve conduit.…”
Section: Chitosan As a Tool For Neurotrophic Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation